The immigrant-native gap in risk and time preferences in Germany: levels, socio-economic determinants, and recent changes - Sumit S. Deole; Marc Oliver Rieger (Journal of Population Economics, 2022)
We present new descriptive evidence on the immigrant-native gap in risk and time preferences in Germany, one of immigrants' most preferred destination countries. Using the recent waves of the Socio-Economic Panel (SOEP) dataset, we find that the immigrant-native gap in risk preferences has widened for recent immigration cohorts, especially around the time of the 2015 European Refugee Crisis. We attribute the recent widening to decreased assimilation rates of new immigrants caused by reduced integration due to sudden increases in immigrants flows from culturally diverse parts of the world, particularly around the year 2015. We also find that the immigrant-native gap varies across different migrant groups: "Opportunity seekers," which we define as economic immigrants who intend to stay in Germany only temporarily, are very similar in their risk preferences to natives. Other immigrants, however, are substantially more risk averse than natives. A smaller gap in risk preferences is also found among migrants who are female, highly educated, proficient in the host language, self-employed, and working in predominantly high-skilled jobs. Concerning time preferences, a noticeably large immigrant-native gap is evident, but the gap does not vary across most individual-level socio-economic variables.
Keywords: J61; D91; 330; Risk aversion; Time discounting; Immigration; Assimilation